Long PCR-based technique for detection of transposon insertions in and around cloned genes of Drosophila melanogaster. - Gordadze, A.V.; Benes, H. (BioTechniques, 1996)
A technique to detect a transposable element insertion greater than 5 kb away from a given gene-specific site is described. PCR is performed on genomic DNA isolated from a pool containing one heterozygous mutant fly, carrying an amplifiable allele, within a pool of 100 flies with no amplifiable sequences. A model procedure for optimizing PCR conditions and a test for primer ability to amplify sequences greater than 5 kb in length from very low dilutions of mutated sequences within non-amplifiable wild-type genomic DNA are described. The optimal annealing temperature range is shown to be as narrow as a 2 degrees C interval. Careful primer design is critical to the success of detection. Under the conditions developed, we detected many local transposable element hopping events, averaging about 3-4 per 50 flies, with the size of the PCR products being in the range of 100-6000 bp. In some cases, even larger (up to 8000 bp) bands were detected.